Concise Review: Human‐Animal Neurological Chimeras: Humanized Animals or Human Cells in an Animal?. (28th January 2019) - Crane, Andrew T.; Voth, Joseph P.; Shen, Francis X.; Low, Walter C.
Abstract: Blastocyst complementation is an emerging methodology in which human stem cells are transferred into genetically engineered preimplantation animal embryos eventually giving rise to fully developed human tissues and organs within the animal host for use in regenerative medicine. The ethical issues surrounding this method have caused the National Institutes of Health to issue a moratorium on funding for blastocyst complementation citing the potential for human cells to substantially contribute to the brain of the chimeric animal. To address this concern, we performed an in‐depth review of the neural transplantation literature to determine how the integration of human cells into the nonhuman neural circuitry has altered the behavior of the host. Despite reports of widespread integration of human cell transplants, our review of 150 transplantation studies found no evidence suggestive of humanization of the animal host, and we thus conclude that, at present, concerns over humanization should not prevent research on blastocyst complementation to continue. We suggest proceeding in a controlled and transparent manner, however, and include recommendations for future research with careful consideration for how human cells may contribute to the animal host nervous system.Stem Cells 2019;37:444–452 Abstract : Blastocyst complementation has potential to generate fully functioning human organs and tissues for transplantation into patients. A major concern arising over this process is the contribution of human cells to the central nervous system of host animals. This review investigates pre‐clinical studies of human‐animal neurological chimerism and suggests concerns over humanization of the host should not prohibit funding for future studies.